DEVELOPMENT OF A MOBILE APPLICATION BASED HEALTH TRACKING SYSTEM (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Nowadays, with the development of mobile technology, different perspectives have occurred in the system of health tracking. With the diseases requiring continuous follow-up, in the current situation, a patient had to stay in the hospital. Patients’ physiological data are able to be monitored via the mobile technologies wherever the patients are (at home, at work, on road …etc.). With this study, the patients’ ECG data can be monitored remotely by not only the patients themselves but also their companions and doctors. This kind of mobile health applications increases the quality and productivity of health services. The developed application with Android Studio takes the data from Arduino Card using e-Health sensor shield via Bluetooth technology. The taken data are recorded on the web environment utilizing this application. Then, these data can be accessed by patients’ companions or doctors and the web-based monitoring of the patients is provided.